Rancang Bangun Aplikasi Pengolahan Data Nilai Siswa Berbasis Web dengan Metode Agile pada Sekolah Dasar 011 Kebun Agung: Design and Construction of a Web-Based Student Grade Data Processing Application Using the Agile Method at Kebun Agung 011 Elementary School - Aji, Muhamad Aji Romadhon (Universitas Muhammadiyah Riau, 2025)
Elementary schools are formal educational institutions for children aged 6–12 years and play a crucial role in the early stages of education. With the rapid advancement of information technology across various sectors, including education, the integration of technology into school administrative processes has become increasingly important—particularly in managing student grade data. This study was conducted to provide a solution for SD 011 Kebun Agung by developing a web-based student grade management system that enables faster, more accurate, and more accessible input, processing, and dissemination of grade information for teachers and parents. The application was designed and developed using the Agile software development methodology, with Python as the programming language and Django as the framework, and was deployed on the PythonAnywhere platform for online access. Testing using the black-box method indicated that all system features operated effectively in accordance with user requirements. Moreover, interviews with teachers indicated that the application significantly improved the efficiency of grade processing and optimized the communication of academic information to parents. Therefore, the system developed through this study successfully accommodates the needs of SD 011 Kebun Agung in enhancing the efficiency and effectiveness of student grade data management.